Selective Involvement of a Subset of Spinal Dorsal Horn Neurons Operated by a Prodynorphin Promoter in Aβ Fiber-Mediated Neuropathic Allodynia-Like Behavioral Responses in Rats - Ishibashi, Tadayuki; Yoshikawa, Yu; Sueto, Daichi; Tashima, Ryoichi; Tozaki-Saitoh, Hidetoshi; Koga, Keisuke; Yamaura, Ken; Tsuda, Makoto (Frontiers in Molecular Neuroscience, 2022)
Mechanical allodynia (pain produced by innocuous stimuli such as touch) is the main symptom of neuropathic pain. Its underlying mechanism remains to be elucidated, but peripheral nerve injury (PNI)-induced malfunction of neuronal circuits in the central nervous system, including the spinal dorsal horn (SDH), is thought to be involved in touch-pain conversion. Here, we found that intra-SDH injection of adeno-associated viral vectors including a prodynorphin promoter (AAV-PdynP) captured a subset of neurons that were mainly located in the superficial laminae, including lamina I, and exhibited mostly inhibitory characteristics. Using transgenic rats that enable optogenetic stimulation of touch-sensing Aβ fibers, we found that the light-evoked paw withdrawal behavior and aversive responses after PNI were attenuated by selective ablation of AAV-PdynP-captured SDH neurons. Notably, the ablation had no effect on withdrawal behavior from von Frey filaments. Furthermore, Aβ fiber stimulation did not excite AAV-PdynP+ SDH neurons under normal conditions, but after PNI, this induced excitation, possibly due to enhanced Aβ fiber-evoked excitatory synaptic inputs and elevated resting membrane potentials of these neurons. Moreover, the chemogenetic silencing of AAV-PdynP+ neurons of PNI rats attenuated the Aβ fiber-evoked paw withdrawal behavior and c-FOS expression in superficial SDH neurons. Our findings suggest that PNI renders AAV-PdynP-captured neurons excitable to Aβ fiber stimulation, which selectively contributes to the conversion of Aβ fiber-mediated touch signal to nociceptive. Thus, reducing the excitability of AAV-PdynP-captured neurons may be a new option for the treatment of neuropathic allodynia.